Economic and mathematical modeling of second-tier banks management - Mynzhasarov, R.I.; Sikhimbayeva, D.R.; Zhumabekova , M.B. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the study of the problems of the management system of banking and second-tier banks in Kazakhstan in modern conditions. The purpose of the study is the development of evidence-based recommendations for improvement of management in the banking sector. On the basis of economic and mathematical modeling of second-tier banks in a stable economy and during the crisis, the most priority directions of its development are developed and ways of solving modern problems of the Bank in the conditions of uncertainty and strategies to minimize Bank risks are proposed. The results of the forecasts of the secondtier banks in the crisis for the period of 2019–2021 are presented, taking into account the negative, moderate and positive scenarios of development of banks. The built dependencies showed the need to develop a new strategy of the Bank in order to enhance banking activities by attracting additional funds by expanding loan capital, investment resources, deposits of legal entities and individuals. The main results of the research are as follows: economic and mathematical models for determining the effectiveness of management of banks of the second level were proposed; evidence-based recommendations for the improvement and development of management in the banking sector and priorities for the development of banking management from the standpoint of its functional dependence in the economic policy of Kazakhstan were developed.